Nutritional supplements for muscle hypertrophy: Mechanisms and morphology—focused evidence - Manescu, A. M.; Hangu, S. S.; Manescu, D. C. (Nutrients, 2025)
Nutritional supplementation is widely used in resistance training, yet assessment of "hypertrophy" is often confounded by body-composition surrogates. This narrative review, anchored in mechanistic plausibility, integrates trials reporting morphology-direct outcomes (ultrasound/MRI). Across 46 eligible trials, protein/essential amino acids (EAA) showed consistent benefits when daily intake was <1.6 g·kg-1·day-1 or when per-meal leucine provision was <2-3 g; effects plateaued once intakes exceeded ~2.0 g·kg-1·day-1. Creatine monohydrate (3-5 g·day-1, with or without loading) produced measurable increases in muscle thickness or cross-sectional area in interventions lasting =8-12 weeks, mediated by enhanced training volume and quality. ß-hydroxy-ß-methylbutyrate (HMB, 3 g·day-1) demonstrated conditional utility during high training stress or caloric deficit, but was largely neutral in well-fed, resistance-trained cohorts. Adjuncts such as omega-3 fatty acids (1-2 g·day-1), citrulline (6-8 g pre-exercise), and collagen (10-15 g·day-1 plus vitamin C) primarily facilitated training tolerance, recovery, or connective-tissue adaptation, rather than driving hypertrophy directly. A tiered model is proposed: protein/EAA as the foundation, creatine as amplifier, HMB as conditional agent, and adjuncts as facilitators. Methodological heterogeneity, short intervention length, and inconsistent imaging protocols remain limiting factors, underscoring the need for standardized ultrasound/MRI and adequately powered, preregistered trials.